Analisis Efektivitas Penambahan Kapasitas Pintu Air Manggarai Untuk Pengendalian Banjir Di Wilayah Sungai Ciliwung - Anggraini, Nimas Ayu; Dermawan, Very; Purwati, Endang (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
DKI Jakarta Province consists of 5 cities and 1 district. At the north part of Jakarta there are beaches which became the estuary of 13 rivers and 2 canals. Ciliwung is the main river that has an effect on the lives of people in Jakarta. The Ciliwung river flows towards to BKB. Manggarai sluice gate is located at the upstream of BKB to control Ciliwung river flow. This study was conducted by giving two addition of Manggarai sluice gate, each dimension of additional gate is 3.4 m x 8.1 m and 5 m x 5.3 m. Discharge calculations for hydrology analysis used Log Pearson III while hydraulics analysis used software HECRAS 4.1.0. Discharge data at AWLR MT Haryono control point recorded on January 21st,2013 showed 287.876 m 3 /sec. From the data, sluice gate simulations conducted with 8 alternatives opening gates. In this study showed the most effective results for Q2th and Q5th with opening gates 2 m (alternative 4), Q10th with opening gates 4 m (alternative 5), Q20th and Q25th with opening gates 6 m (alternative 6), Q50 and Q100th with maximum gates opening (alternative 8).Keywords: Sluice Gate, Simulation, Gate Operation, Opening Gate